A novel broad-spectrum bacteriophage cocktail against methicillin-resistant Staphylococcus aureus: Isolation, characterization, and therapeutic potential in a mastitis mouse model - Maryam Banar; Haniyeh Kamyab; Narges Torkashvand; Taghi Zahraei Salehi; Zargham Sepehrizadeh; Ahmad Reza Shahverdi; Mohammad Reza Pourmand; Mohammad Hossein Yazdi (PLoS ONE, 2025)
Bovine mastitis is a considerable challenge within the dairy industry, causing significant financial losses and threatening public health. The increased occurrence of methicillin-resistant Staphylococcus aureus (MRSA) has provoked difficulties in managing bovine mastitis. Bacteriophage therapy presents a novel treatment strategy to combat MRSA infections, emerging as a possible substitute for antibiotics. This study evaluated the therapeutic potency of a novel bacteriophage cocktail against MRSA mastitis. Two new bacteriophages (vB_SauR_SW21 and vB_SauR_SW25) with potent lytic activity against MRSA were isolated and characterized. The one-step growth curve displayed a rapid latent period (20–35 min) and substantial burst size (418 and 316 PFU/ cell). In silico analyses have confirmed the absence of antimicrobial resistance or virulence factor-encoding genes within their genomes. According to the results, combining these phages augmented their host range and virulence. The phage cocktail significantly reduced bacterial burden in a BALB/c mastitis model, demonstrating efficacy comparable to antibiotic treatment. Moreover, its administration led to decreased concentrations of IL-1β and TNF-α compared to the negative control group. The bacteriophage cocktail (SW21-SW25) exhibits a promising profile for therapeutic applications and may represent a novel substitute to antibiotics for managing MRSA bovine mastitis.